2017
DOI: 10.1155/2017/7981549
|View full text |Cite
|
Sign up to set email alerts
|

A Low Psoas Muscle Index before Treatment Can Predict a Poorer Prognosis in Advanced Bladder Cancer Patients Who Receive Gemcitabine and Nedaplatin Therapy

Abstract: Introduction. Gemcitabine and cisplatin (GC) is a gold-standard first-line systemic chemotherapy for advanced urothelial carcinoma (UC). However, it may cause severe adverse effects such as renal toxicity, gastrointestinal toxicity, and neurotoxicity. Sarcopenia is the age-related loss of skeletal muscle mass. A correlation between sarcopenia and the oncological prognosis has been reported. In UC, several studies have noted that patients with sarcopenia had a greater incidence of complications and worse surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 15 publications
1
33
0
1
Order By: Relevance
“…There as well, a low PMI was associated with a poorer oncological outcome than a high PMI (9,10). Other recent studies have revealed that sarcopenia is a risk factor for postoperative complications or a poor survival in some solid cancers.…”
Section: Discussionmentioning
confidence: 89%
“…There as well, a low PMI was associated with a poorer oncological outcome than a high PMI (9,10). Other recent studies have revealed that sarcopenia is a risk factor for postoperative complications or a poor survival in some solid cancers.…”
Section: Discussionmentioning
confidence: 89%
“…However, most often, only a small range (several centimetres) of a muscle is scanned to reduce the radiation dose. In this case, area and volume measurements need to be normalized, for example, to the square of the body height [24] , [39] , [52] , [53] , to be representative regarding fatty infiltration assessment. The trunk muscle area at the L4-5 level or 5 cm above is highly correlated with the total body skeletal muscle volume (r 2 > 0.8) [54] .…”
Section: Methods Of Quantitative Ct Imagingmentioning
confidence: 99%
“…Four studies evaluated the prognostic role of sarcopenia in patients with inoperable advanced bladder cancer ( Table 1 ) [ 51 , 52 , 53 , 54 ]. Because upper tract urothelial carcinoma is histologically and biologically similar to bladder cancer, three of them included advanced upper tract urothelial carcinoma in their cohorts [ 51 , 52 , 54 ].…”
Section: Prognostic Role Of Sarcopenia In Bladder Cancermentioning
confidence: 99%
“…Taguchi et al reported that sarcopenia is an independent predictor for shorter CSS in metastatic urothelial carcinoma patients receiving systemic chemotherapy as the first-line therapy [ 52 ]. Kasahara et al showed the prognostic significance of sarcopenia in advanced bladder cancer patients receiving gemcitabine and nedaplatin therapy [ 53 ]. In addition, Abe et al could not confirm the significance of sarcopenia in predicting OS, but they showed that SMI stratified by BMI was an independent predictor for shorter OS [ 54 ].…”
Section: Prognostic Role Of Sarcopenia In Bladder Cancermentioning
confidence: 99%